The Influence of Packaging, Price, and Promotion Strategies on Product Purchasing Decisions in The Indo Jaya Tempeh Industry - Melati Melati; Irham Natsir K; Sri Widati (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
This study aims to determine what is achieved in this study is to determine and analyze the effect of packaging, price, and promotion strategy on purchasing decisions for Tempe Indo Jaya products in Sendang Mulyasari Village, the effect of plastic Packaging on purchasing decisions for Tempe Indo Jaya products, the effect of price on product purchasing decisions Tempe Indo Jaya and the influence of promotional strategies on purchasing decisions for Tempe Indo Jaya products. The method in this Research is a descriptive analysis performed to explain the effect of product attributes and product warranties on purchasing decisions. Multiple linear regression analysis was used to statistically test the effect of product attributes and warranties on purchasing decisions. Studies on Tempe Indo Jaya home industry. This analysis method is based on the results of a questionnaire on the variables of this study which have been converted by clarifying answers on a Likert scale. Data processing was carried out By using the SPSS version 25 program. The results of this study show that the Promotion Strategy has a positive and significant effect on purchasing decisions in the Tempe Indo Jaya Industry, Sendang Mulyasari Village, Tonggauna District. The better the Promotion Strategy, the better the decision to purchase.